Evaluation of calcium ion release in calcium hydroxide prototype as intracanal medicament - Atia N. Sidiqa; Myrna N. Zakaria; Ira Artilia; Zwista Y. Dewi; Arief Cahyanto (Journal of Dentomaxillofacial Science, 2020)
Objective:Calcium Hydroxide (Ca(OH)2 ) has been widely used in many dental treatments such as pulp capping, dentin hypersensitivity and as an endodontic intracanal medicament. Ca(OH)2 is highly alkaline, has antimicrobial, and remineralization action by releasing Ca2+ and OH. Ca2+ release plays an important role in cell proliferation and remineralization of hard tissue healing. Indonesian limestone can be synthesized to produce Ca(OH)2 that can be an alternative to commercial Ca(OH)2 available. Therefore this study aimed to synthesized a Ca(OH)2 prototype and evaluate the Ca2+ released by the Ca(OH)2 prototype.Material and Methods: Ca(OH)2 prototype was synthesized from limestone by calcination process and characterized by XRD and FTIR. The Ca(OH)2 prototype was then manipulated to a pasta form by mixingÂ the powder with distilled water in 0.8 w/p ratio then inserted to a polyethylene tubed (2x10mm) using and immersed in 10 ml distilled water. Samples were divided into three groups for different periods of Ca2+ evaluation (1, 7 and 14 days). The Ca2+ concentration released was measured by a Spectrophotometer (DIRUI DR-7000D). Data obtained were analyzed by Anova.Results: The observations on one day immersion was 3.589 mg/dL, the observation for seven days was 3.736 mg/dL, and for 14 days was 3.850 mg/dL. Statistically p<0.05.Conclusion: Calcium hydroxide prototype released a sustainable amount of Ca2+ up to 14 days with the highest concentration achieved on day 14th.